Valuating Payoff Streams under Unequal Discount Factors - Hannu Salonen; Hannu Vartiainen (Aboa Centre for Economics (ACE), 2007)
We study repeated prize allocation problem when the discount factors f the agents are not equal. It is shown that the feasible set of payoffs is not well behaved. In particular, it is not convex as it contains holes and caves. The Pareto frontier is everywhere discontinuous and there is an open subset of discount factors such that the feasible set is totally disconnected.
Keywords: C60; C70; 330; payoffs; differentiated discount factor; repeated games